VISUALISASI DAN ANALISIS DATA PENJUALAN WARUNG BLASTER DAN WARUNG BHINEKA SANUR MENGGUNAKAN MICROSOFT POWER BI MUHAMMAD DEDE FITRIAWAN - dede, Muhammad dede fitriawan (PT. ZIVANA CENDEKIAWAN BANGSA, 2024)
Microsoft Power BI is Business Intelligence software made by Microsoft that allows users to get data from various sources. This tool is used to process data in more detail using more active and varied graphics. This application can visualize data that has been entered, or data that has been connected to other systems. Microsoft Power BI can make it easier to control and monitor data. The main goal of data visualization is to communicate information clearly and efficiently to users via the selected form of information graphic. A graph is a depiction of the ups and downs of a condition or existing data with lines or pictures. Warung Blaster and Warung Bhineka Sanur are restaurants that combine Asian, Italian and Western food. In processing sales data, Warung Blaster and Warung Bhineka Muda Sanur still carry out manual processes in Microsoft Excel. This research uses qualitative research with the literature study method. The results of the research are that Warung Blaster and Warung Bhineka Muda Sanur are able to implement Business Intelligence based on a dashboard system to make it easier to produce sales reports and can help analyze problems and determine the performance of each business.